The Determination of the Relationship Between Academic Procrastination and Attitudes Towards Sports of University Students Studying Sports Science - Sanlav, Ramazan; Bulgurcuoğlu, Ahmet Nusret; Tazegül, Ünsal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: It is suggested that there is a relationship between students’ academic procrastination behavior and their attitudes towards sports. This study aims to explain how this relationship is. The aim of this study is to determine the relationship between academic procrastination and attitudes towards sports of students studying at Mardin Artuklu University School of Physical Education and Sports. Methods: While the universe of the study was formed by the students studying at Mardin Artuklu University School of Physical Education and Sports; The sample consists of 182 students who voluntarily agreed to participate in the study. Attitude towards Sports Scale and Academic Procrastination Scale were used as data collection tools in the study. SPSS 20 package program was used to analyze the obtained data. The "Kolmogorov-Smirnov" test was used to determine that the data had a normal distribution, and "ANOVA Homogeneity of Variance” test was used to evaluate whether the data were homogeneous, and it was determined that the data had a homogeneous and normal distribution. In the analysis of data, descriptive statistics, one-way analysis of variance and correlation analysis were applied. Results: At the end of the study, it was seen that the students of Physical Education and Sports department got higher scores in the field of psycho-social development, physical development and total sports attitude, and the students of the Sports Management department in the field of mental development. When the sub-dimensions of academic procrastination and attitude towards sports were compared according to the departments, no statistically significant difference was found in any dimension. Conclusion: As a result, students have many projects to do and many exams to complete throughout their academic life. In this process, students in undergraduate education generally have to devote most of their time to study and education and training life for a successful future.